Business Feasibility Analysis of Processed Sweet Potato Products at MSME Karya Indah Bandorasa Wetan - Astrid Khalda Kusuma Andini; Farhan Nurfarizi; Dwi Purnomo (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Sweet potato processing is a vital part of the local economy. In this study, the business costs incurred and feasibility of processing sweet potato product businesses in the Malaysian Small and Medium Enterprises (MSME) Karya Indah in Bandorasa Wetan are analyzed. The research is based on a census technique, namely, the MSME Karyan Wetans, which is used as the population and sample in the research. The business costs are calculated to calculate various costs associated with running a business consisting of fixed costs and variable costs. The acceptance feasibility ratio was found to be 1.455, so it is greater than 1 and is in the feasible and feasible category. This research offers practical guidance for MSMEs in assessing their operational efficiency and helps business owners make informed decisions about investment and expansion. Furthermore, it contributes to the broader understanding of sustainable business practices in the agricultural processing sector, specifically focusing on sweet potato products. Moreover, analyzing the impact of technological improvements or more efficient production methods on reducing costs and increasing productivity could provide valuable insights for enhancing business operations.